Internal Nutrient Loading Controls Macroalgal and Cyanobacterial Succession in a Coastal Lagoon Restored by Managed Realignment of Agricultural Land - Thorsen, Sandra W.; Holmer, Marianne; Quintana, Cintia O.; Valdemarsen, Thomas; Kristensen, Erik (Frontiers in Marine Science, 2021)
Managed realignment (MR) has been increasingly applied as an adaptation strategy to sea level rise in low-lying coastal areas, but the ecological consequences after flooding agricultural land with seawater are not well known. The restored Gyldensteen Coastal Lagoon represents one of the largest MR projects in Europe to date. The area served as agricultural land for about 150 years before being deliberately flooded with seawater in 2014. This study monitored for five years the succession of macroalgae and benthic cyanobacteria driven by changing internal nutrient (DIN = NH4+ + NO2- + NO3-, DON = dissolved organic nitrogen and DIP = PO43-) loadings in the lagoon after flooding. A massive bloom of opportunistic green macroalgae (dominated by Cladophora) occurred during the first year as response to a substantial loading of DIN and DIP from the newly flooded soils. The macroalgal cover was sparse the following years and the species richness increased with lower loading of particularly DIN. A cyanobacterial bloom controlled by declining DIN and steady DIP concentrations in the water dominated the lagoon and covered all solid surfaces four years after flooding. Highest macroalgal species richness with dominance of perennial Fucus vesiculosus and Agarophyton vermiculophylla was recorded five years after flooding following a temperature-induced stimulation of soil nitrogen transformation leading to increased water column DON concentrations and DIN:DIP ratios. The lagoon remains therefore at an unstable tipping point where small and random changes in the DIN:DIP ratio control the balance between blooms of benthic cyanobacteria and high macroalgal species richness. Future MR projects involving agricultural land should prepare the soil to prevent algal blooms driven by sustained internal nutrient loading. Particularly P loading should be avoided to minimize the chances for recurrent blooms of benthic cyanobacteria.